UPAYA MENINGKATKAN KECERDASAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN DI TAMAN KANAK-KANAK ISLAM CITRA MANDIRI KOTA SERANG - Sari, Yuli Eka; Laili, Mahsiani Mina; Surya, Havid (LPPM Universitas Bina Bangsa, 2024)
This research focuses on the storytellyng method in improving the social-emotional intelligence of children aged 5-6 years at Citra Mandiri Islamic Kindergarten. The purpose of this study is to find out the social-emotional intelligence of children aged 5-6 years, to find out the benefits of the role-playing method in increasing the social-emotional intelligence of children aged 5-6 years and to find out whether this role-playing method is effective in increasing the social-emotional intelligence of children after 5-6 years at Citra Mandiri Islamic Kindergarten. The method in this study is qualitative descriptive. The data collection techniques in this study are observation, intervuews and documentation. The results of tus study show that the role-playing method is proven to be effective in increasing the social-emotional intelligence of children aged 5-6 years at Citra Mandiri Islamic Kindergarten. It can be seen that from the 11 children, there are 3 BB children, 3 MB Children, 3 BSH children, and 2 BSB children. Therefore, it can be concluded that the role-playing method is quite effective in increasing the social-emotional intelligence of children aged 5-6 years at Citra Mandiri Islamic Kindergarten with quite satisfactory results